The adoption of laser land leveler technology and its impact on groundwater use by irrigated farmland in Punjab, Pakistan - Sheikh, Asjad Tariq; Mugera, Amin; Pandit, Ram; Burton, Michael; Davies, Stephen (Wiley, 2022)
This paper investigates the factors that influence the adoption of laser land levelers and their impact on groundwater usage in the Punjab Province of Pakistan. A farm household survey of 504 agriculture producers was conducted in 2019. A discrete-time duration model is used to investigate factors influencing the speed of adoption and an endogenous switching regression (ESR) model is used to evaluate its impact on groundwater usage. About 70% of the surveyed households adopted the technology, and the average time to adoption was 9 years. Key factors accelerating the speed of adoption include strong legal land rights, access to information about the technology, and exposure to the technology. In contrast, long distance to rental market deaccelerates the speed of adoption. The adoption of laser land leveler reduced groundwater use by about 23%. The results imply that institutional arrangements, such as improving access to extension services, exposure to innovation, and legal land rights, can enhance the adoption and diffusion of the technology and conserve groundwater.